1982
DOI: 10.1002/app.1982.070270716
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ultraviolet light on the mechanical properties of polyethylene and polypropylene films

Abstract: SynopsisMeasurements were made of dynamic mechanical response spectra and stress-strain properties at room temperature on films of isotactic polypropylene and low-density polyethylene prior and after ultraviolet irradiation in a Xenotest 450 apparatus. The period of irradiation that caused a deep deterioration of ultimate mechanical properties influenced the dynamic mechanical properties only insignificantly. This is attributed to the heterogeneous nature of the photo-oxidative degradation process which is con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
0

Year Published

1984
1984
2000
2000

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(35 citation statements)
references
References 9 publications
4
31
0
Order By: Relevance
“…On the other hand, if the modulus is measured with the Instron dynamometer, already at low deformations a small stress may cause an increase in the deformation; consequently the modulus in the transverse direction may decrease, while the anisotropy of the moduli may increase. This effect is still more pronounced in the tensile strength determination, when a relatively small strain is already sufficient to bring about catastrophic break This is in agreement with the mechanism of failure of polypropylene and polyethylene films examined in greater detail by Raab et al [1]. The anisotropies of tensile strength and of the modulus of undrawn polypropylene film are small and they almost do not differ from each other.…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…On the other hand, if the modulus is measured with the Instron dynamometer, already at low deformations a small stress may cause an increase in the deformation; consequently the modulus in the transverse direction may decrease, while the anisotropy of the moduli may increase. This effect is still more pronounced in the tensile strength determination, when a relatively small strain is already sufficient to bring about catastrophic break This is in agreement with the mechanism of failure of polypropylene and polyethylene films examined in greater detail by Raab et al [1]. The anisotropies of tensile strength and of the modulus of undrawn polypropylene film are small and they almost do not differ from each other.…”
Section: Resultssupporting
confidence: 68%
“…We assume that such an effect is represented by the presence of micro-or macrodefects, or of longitudinal cracks between bundles of microfibrils, if a fibrillar structure according to Peterlin is assumed [5]. Flaws such as supposed by, e. g., Raab et al [1] may affect insignificantly the magnitude of the sonic modulus along the axes of microfibrills (direction of drawing), but in the transverse direction they may cause acoustic inhomogeneity, and thus affect the sonic modulus. They certainly do reduce the tensile strength and elongation-at-break in the transverse direction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of natural weathering on mechanical properties and chemical structure of Ni quenchers combined with UV absorber-stabilized LDPE were also studied by Akay et al 4 No simple correlation was found to exist between the development of carbonyl groups and strain at break which was one of the most important parameters in following UV stability. It was also shown by Raab et al 5 that the chemical changes might not greatly influence the bulk properties, such as complex modulus, but they significantly decreased strain at break because fracture followed the weakest path in the material. 5 Hence, in UV stability assessments, the change in elongation at break commonly is used rather than other mechanical properties.…”
Section: Introductionmentioning
confidence: 87%
“…It was also shown by Raab et al 5 that the chemical changes might not greatly influence the bulk properties, such as complex modulus, but they significantly decreased strain at break because fracture followed the weakest path in the material. 5 Hence, in UV stability assessments, the change in elongation at break commonly is used rather than other mechanical properties. An initial increase in residual elongation (RE: the ratio of strain at break at the given UV exposure time to strain at break of unexposed sample) followed by steady decrease was described as chain stiffening effect.…”
Section: Introductionmentioning
confidence: 87%